IKON, INDEKS, DAN SIMBOL DALAM MEME DI INSTAGRAM - Rini Prismayanti; T. Thyrhaya Zein; Hariadi Susilo (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This research discusses memes in digital form which are spread via the internet as a medium for conveying messages in a new form. The aim of this research is to describe and interpret the signs and meanings contained in memes, especially on the social media Instagram @hai.dudu, using Peirce's semiotic concept which focuses on icons, indices and symbols. Next, we use Barthes' semiotic concept which focuses on the meaning of denotation, connotation and myth. The method for collecting data is qualitative descriptive which focuses on data in words and images. This research uses documentation studies and interviews for data analysis using an interactive model. The research results showed that icons were found that depicted roles marked with special characters such as the characters dudu, momo, side. Next, icons were found depicting animals, objects, food and places. The index found based on expressions in images and text has a cause and effect relationship in producing meaning. In symbols, it is found to symbolize an event or action symbol, and is symbolic based on a word that has been agreed upon by the general public.